Solar Radiation and Climate Experiment (SORCE) X-Ray Photometer System (XPS): Final Data-Processing Algorithms - Woods, Thomas N.; Elliott, Joshua (Solar physics, 2022)
The X-ray Photometer System (XPS) is one of four instruments onboard NASA’s Solar Radiation and Climate Experiment (SORCE) mission. The SORCE spacecraft operated from 2003 to 2020 to provide key climate-monitoring measurements of total solar irradiance (TSI) and solar spectral irradiance (SSI). The XPS is a set of photometers to measure the solar X-ray ultraviolet (XUV) irradiance shortward of 34 nm and the bright hydrogen emission at 121.6 nm. Each photometer has a spectral bandpass of about 7 nm, and the XPS measurements have an accuracy of about 20%. The updates for the final data-processing algorithms for the XPS solar-irradiance data products are described. These processing updates include improvements for the instrumental corrections for background signal, visible-light signal, and degradation trending. Validation of these updates is primarily with measurements from a very similar XPS instrument onboard NASA’s Thermosphere-Ionosphere-Mesosphere-Energetics-Dynamics (TIMED) mission. In addition, the XPS Level 4 spectral model has been improved with new reference spectra derived with recent XUV observations from NASA’s Solar Dynamics Observatory (SDO) and Miniature X-ray Solar Spectrometer (MinXSS) cubesat.